Patient experience of an integrated care model in a family practice clinic & FQHC. (September 2020) - Koehler, Aubry N; Sudano, Laura E; Ip, Edward; Davis, Stephen W; Marion, Gail S; Kirk, Julienne K
In order to investigate the patient experience of integrated behavioral health care in primary care settings, we implemented a patient cohort model from a combined site sample (N = 727) consisting of a family practice clinic and a Federally Qualified Health Center. Patient experience was measured using 12 questions from a validated measure, the Agency for Healthcare Research and Quality's Consumer Assessment of Health Care Providers and Systems (CAHPS®), Home and Community Based Services version, and six additional questions about interactions with an integrated behavioral health care team. We assessed bivariate relationships between satisfaction with integration and the clinic practice and self-reported physical health or self-reported mental/emotional health. We also utilized multiple regression to evaluate this relationship. Our analyses showed a statistically significant and small to moderate direct correlation between patients' self-reported health (both physical and mental/emotional health) and their ratings of the practice as a whole (p = .0003), such that patients who rated their physical and/or mental/emotional health as better were more likely to rate their overall satisfaction with the practice higher. The results of this study suggest that primary care patients with only mild to moderate health conditions (physical and/or mental/emotional) may experience greater satisfaction with integrated behavioral health care than patients with multiple and/or severe health conditions. In contrast, patients with multiple and/or severe health conditions may experience lower satisfaction with integrated behavioral health care and may be better served through higher levels of care.